The Influence of Self-Confidence on Student Learning Outcomes: A Study on 10th Grade Students in High Schools in The Bebandem District, Karangasem Regency, Bali Province - I Ketut Wiriawan (International Journal Labs, 2023)
Students who have general self-confidence will be able to overcome fears or negative thoughts. Usually, students who have a high level of self-confidence will also have high academic achievement as well. While doing observation, the researcher found that some of the students have problems with their self-confidence. There were several phenomena already found, such as (1) the students were not able to express their thoughts and opinions when the students did the speaking activities. (2) the students were not confident while answering the question given. This study aimed to determine the correlation between students’ self-confidence toward student learning achievement in English language learning in tenth-grade students in the Bebandem district. This study is an ex-post-facto research design with a correlational technique and questionnaire method with 73 students in tenth grade in the Bebandem district were a sample of this study. Questionnaires of Students’ Self-confidence and documentation toward students’ report cards were used to collect the data then Descriptive statistics, and determination tests were used to analyze the data. Based on the data analysis it was found that there is a significant correlation between students’ self-confidence toward students’ learning achievement in English learning of tenth grade in the Bebandem district with a correlation value (0.099) and p-value (0.023) > 0.05. Based on the determination test is only 0.98 students’ self-confidence can explain the variance of learning achievement and 99.02% predicted by another variable that not examined in this study. The results of this study are by the theory from previous studies which mostly obtained results that there was a significant correlation between students’ self-confidence and learning achievement.